Supply chain analysis of fresh fruits and vegetables (FFV): Prospects of contract farming - Arumugam, Nalini; Mohamed Arshad, Fatimah; Chiew, Eddie Fook Chong; Zainal Abidin, Mohamed (Czech Academy of Agricultural Sciences, 2010)
The paper examines the factors that lead farmers to participate in c the contract farming in the Peninsular Malaysia. The primary data was collected through a survey using a questionnaire on the total of two hundred and eight farmers from various states in Malaysia. The study utilizes the stratified sampling method. Both descriptive and inferential statistics were used to analyze the data. The survey identified forty-one contract farmers. Factor analysis was carried out to identify the factors that lead farmers to participate in the contract farming. Based on the analysis, five factors were identified as the reasons for contracting, namely, market stability, and access to marketing information and technology, transfer of technology to improve farming practices, access to inputs and indirect benefit. Contract farming or contract arrangements can be a valuable source of an additional income and knowledge that can be employed to enhance the productivity of the entire farming enterprise.